Skiing quality analysis of recreational skiers based on IMU data and self-assessment - Kranzinger, Christina; Kranzinger, Stefan; Hollauf, Eva; Rieser, Harald; Stöggl, Thomas (Frontiers in Sports and Active Living, 2024)
Alpine skiing is a popular sport in many countries and holds benefits in terms of health and well-being. At the same time alpine skiing is associated with a certain risk of accidents caused, among other things, by overestimating one’s own skiing skills. Self-assessment of skiing skills is not trivial. Therefore, feedback modalities can be assistive. One feasible option to provide skiers with feedback on their skiing ability are Inertial Measurement Units (IMUs). The aim of this study was to analyse the skiing quality of recreational skiers based on IMU data, collected with the Connected Boot sensor system with a living lab approach to investigate whether the skiing quality score delivers reasonable results for recreational skiers. The system has been developed with expert skiers and so far has not been validated with recreational skiers. Therefore, we aimed to investigate whether the objective skiing quality score of the Connected Boot corresponds to the self-assessed carving ability and to analyse changes in the assessment before and after the study. In total, data from 62 participants who skied with the sensor system were analysed. At the beginning and the end of the study the participants additionally received questionnaires to assess their skiing skills. The results show that there was a strong correlation between the self-reported carving ability and the skiing quality score of the Connected Boot and that the self-reported carving ability before the study was around 1.71 points higher than the algorithm-based skiing quality score. Interestingly, the correlation was higher for female compared to male participants.